2020
DOI: 10.1111/jcmm.15800
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of CD34+ angiogenic stem cells in human first‐trimester decidua and their therapeutic for ischaemic heart disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The incidence rate of heart failure after MI was more than 50% in 5 years. Previous studies have shown that BMSCs ( 17 ), embryonic stem cells ( 18 ), iPSCs ( 19 ), CD34 + angiogenic stem cells ( 10 ) and other MSCs promote blood flow reperfusion of infarcted myocardial tissue, induce angiogenesis in infarcted myocardium, and significantly improve cardiac function. Although MSC transplantation is considered as a promising therapeutic strategy for cardiac remodeling in ischemic heart disease, the effect is not satisfactory in clinical translational research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence rate of heart failure after MI was more than 50% in 5 years. Previous studies have shown that BMSCs ( 17 ), embryonic stem cells ( 18 ), iPSCs ( 19 ), CD34 + angiogenic stem cells ( 10 ) and other MSCs promote blood flow reperfusion of infarcted myocardial tissue, induce angiogenesis in infarcted myocardium, and significantly improve cardiac function. Although MSC transplantation is considered as a promising therapeutic strategy for cardiac remodeling in ischemic heart disease, the effect is not satisfactory in clinical translational research.…”
Section: Discussionmentioning
confidence: 99%
“…After being separated by centrifugation (1,000 rpm/5 min), cells were resuspended in 4 ml DMEM/F12 medium containing 10% FBS, and cultured in an incubator of 37°C, 5% CO2. On the second day, DMSCs were observed in the culture bottle ( 10 ). Similarly, BMSCs were also obtained from female patients (20–30 years old) who needed median thoracotomy in cardiac surgery, stored into a bottle pre-filled with heparin later, quickly transferred to the laboratory for treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They secrete soluble factors with paracrine effects. The therapeutic potential of hPMSCs has been showed in tissue damage repair after ischemic diseases including stroke, and myocardial and cerebral infarctions (7)(8)(9)(10)(11). These studies suggest that hPMSCs-based therapies might be developed for future clinical applications.…”
Section: Introductionmentioning
confidence: 99%